Chapter In Dialogue with Neera - Ramsey-Portolano, Catherine (Biblioteca di Studi di Filologia Moderna, 2022)
This essay examines the evolution of my twenty-year interest in the work of Italian nineteenth-century woman writer Neera (pseudonym for Anna Radius Zuccari), an interest that has culminated with the recent publication Nineteenth-Century Italian Women Writers and the Woman Question: The Case of Neera (2021). My attention to this writer has shifted from an initial exploration of the various characteristics of her production to what I now view as the principal lens for interpreting Neera's role and work: positioning her inside a matrilineal family tree within the Italian literary landscape, one that recognizes the importance of her legacy as literary mother to the numerous Italian women writers that followed. My essay considers Neera's significance today from this perspective while also reflecting upon evolving critical trends within Italianistica.